Conocimiento y aplicación de psicoprofilaxis del trabajo de parto en gestantes del Centro de Salud El Dorado de Puyo año 2013-2014 - Chimbo Malla, Martha Rosalía (2014)
The main purpose of this research was to assess the level of knowledge of pregnancies of the health center of the Golden Canton province of Pastaza Puyo. The purpose is to reduce the caesarean section rate, through the implementation of Psicoprofilaxis technique. The research design was cross-sectional, descriptive literature and field fixed; the method used was a survey and the tool a questionnaire ( Annex 3 ) ; it was applied to 70 to obtain these results; that users at risk are teenagers and another factor is the ; low level of knowledge about the Psicoprofilaxis and no application of it affecting the entire study population. It was concluded that pregnant women attending health center Dorado antenatal checks; 100% do not know about the art of Psicoprofilaxis of labor, have not received information about it; for this reason a proposal is captured in a manual (attached) to contain the benefits and techniques Psicoprofilaxis was prepared; because this techniques good result was obtained by decreasing the risks and complications. A manual was delivered to the leader center health nurse Finally an educational activity for pregnant users of the unit was performed. (Annex 9,10,12) . Keywords : Pregnancy , Childbirth, Psicoprofilaxis